Pengaruh Kompetensi Pedagogik Guru Dan Karakteristik Siswa Terhadap Hasil Belajar Pai Di Smp Negeri 5 Dumai - Ummi Chajaroh (Tamaddun Ummah (JTU), 2022)
This study aims to determine (1) the effect of teacher pedagogic competence on learning outcomes PAI at SMP Negeri 5 Dumai (2) the effect of student characteristics on learning outcomes PAI at SMP Negeri 5 Dumai (3) the effect of teacher pedagogic competence and student characteristics simultaneously on results. Studied PAI at SMP Negeri 5 Dumai. This research is a quantitative research. The research instrument trial took place at SMP Negeri 5 Dumai. The population of this study were students in grade 2. Data collection was carried out by means of a questionnaire. Testing prerequisite analysis includes normality test and linearity test. The data analysis technique used is multiple regression techniques. The results of this study are: (1) There is a positive and significant influence of Teacher Pedagogical Competence on learning outcomes PAI at SMP Negeri 5 Dumai. (2) There is a positive and significant influence on student characteristics on learning outcomes PAI at SMP Negeri 5 Dumai. (3) There is a positive and significant influence on teacher pedagogical competence and student characteristics simultaneously on learning outcomes PAI at SMP Negeri 5 Dumai.